Alkaline citrate reduces stone recurrence and regrowth after shockwave lithotripsy and percutaneous nephrolithotomy - B. Lojanapiwat (2018)
Objective: To evaluate the preventive effects of alkaline citrate on stone recurrence as well as stone growth post-ESWL or PCNL in patients with calcium-containing stones. Materials and Methods: A total of 76 patients with calcium calculi who were stone-free or had residual stones less than 4 mm following ESWL and PCNL were enrolled. All patients were independently randomized into two groups. The treated group (N = 39) was given 81 mEq per day of oral potassium-sodium citrate (27 mEq three times a day), and the untreated group (N = 37) serving as controls. Blood, twenty-four hour urine analysis, and plain KUB were measured and compared at the baseline and after 12 months. Results: At baseline, hypocitraturia was found in 20 of 39 patients (46.05%) of Group I and 15 of 37 patients (40.5%) of Group II. At 12 months, hypocitraturia was found in 3 of 39 (7.69%) and 14 of 37 (37.83%) of Group I and Group II, respectively (p = 0.007). At the 12 month follow-up, of the stone-free group, 92.3% of the treated group and 57.7% of the control group were still stone free. Of the residual stone group, 30.8% and 9.1 % of treated and control group were stone-free, respectively. The increased stone size found in 7.7% and 54.5% of treated and control groups, respectively. Conclusion: Sodium-potassium citrate provides positive effects on stone-forming activities in calcium stone patients suffering from urolithiasis following treatment with ESWL and PCNL procedures at the 12-month follow-up.